Contribution of the Landscape Evaluation in the Study of the Impact on Environment: Application of the Hydro-Québec Method on the Technical Landfill Center of Hamici, Tipaza (Algeria) - Benkahoul, Leila; Aliouche, Sihem; Khettab, Samira (Future Science, 2023)
The development and operation of Technical Landfill Centers (TLC) for urban solid waste lead to significant landscape alterations and have a negative impact on its overall image. However, the Environmental Impact Assessment (EIA) conducted for these TLCs in Algeria do not currently consider the impact of this activity on the landscape as a determining factor for validating the implementation of the landfill site. It is limited, instead, to some mitigation measures. This work addresses the importance of taking into account the impact of TLCs on the visible landscape through EIAs. In this context, the planned landscape integration measures within the scope of the EIA conducted by the Ministry of Environment for the urban solid waste landfill site of Hamici, situated 29 km from the capital Algiers, were examined. In addition, an evaluation the TLC’s impact on the visible landscape after its construction and operation was implemented using the Hydro-Québec method. The results show a high visual impact of the TLC on the landscape unit receiving the landfill cells, a moderate impact on the unit receiving the TLC buildings, and a minor impact on the unit hosting the human settlement, which has the largest number of potential observers in the area. In the light of these findings, it is imperative to integrate landscape evaluation as an operational phase through EIAs before making decisions regarding the siting of landfill sites. This is essential for the purpose of preserving the image of the environment conveyed by the visible landscape.